2015
DOI: 10.1590/0103-8478cr20140705
|View full text |Cite
|
Sign up to set email alerts
|

Restrição fotossintética de plantas de soja sob variação de disponibilidade hídrica

Abstract: RESUMO 004,006,026,164MPa)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 17 publications
4
17
0
7
Order By: Relevance
“…Associated with this, the water limitation results in a dynamic photoinhibition or protective photosynthesis by a limitation in the electron transport in the photosystem II, what leads to a decrease in the photosynthetic rate of short duration (Araújo & Deminicis 2009). Corroborating the present study, it is demonstrated that the drought stress reduces the photosynthetic rate of the plants in function of different levels of photosynthetic photon flux density (Chavarria et al 2015).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Associated with this, the water limitation results in a dynamic photoinhibition or protective photosynthesis by a limitation in the electron transport in the photosystem II, what leads to a decrease in the photosynthetic rate of short duration (Araújo & Deminicis 2009). Corroborating the present study, it is demonstrated that the drought stress reduces the photosynthetic rate of the plants in function of different levels of photosynthetic photon flux density (Chavarria et al 2015).…”
Section: Resultssupporting
confidence: 84%
“…Studies developed with soybean under drought stress conditions report that the maintenance of water content in leaves is essential for productivity (Fioreze et al 2011). Chavarria et al (2015) showed a reduction in the soybean photosynthetic capacity under drought stress, and this condition impacts negatively the crop yield (Naderi et al 2013, Farooq et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Results found by Nascimento et al (2011) in jatobá (Hymenaea courbaril L.) there was a reduction of 31.0% in relation to the plants grown with 100% CC. However, when the water deficit develops in the field, in a slower way, it can impair the vegetative growth since under potting conditions there is limitation to the root growth (CHAVARRIA et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This may result in synthesis of the reactive oxygen species (ROS) that damage the ATP synthase enzyme, delaying the synthesis of ribulose-1,5-bisphosphate (RuBP) and causing a decrease in Ribulose-1,5-bisphosphate carboxylase/oxygenase (rubisco) activity. These are physiological events reflected as lower yield and production components, at lower irrigation depths (Chavarria et al, 2015).…”
Section: Discussionmentioning
confidence: 99%